1996
DOI: 10.1111/j.1469-8137.1996.tb04518.x
|View full text |Cite
|
Sign up to set email alerts
|

Benomyl inhibits phosphorus transport but not fungal alkaline phosphatase activity in a Glomus–cucumber symbiosis

Abstract: SUMMARYShort-tt-rtn effects of benomyl on the arbuscular mycorrhizal fungus GInmus caledonium (Nico!. & Gerd.) Trappe and Gc-rdfman associated with Cucumis sativiis L. were studied by measuring cfFtcts on fungal P transport and on fungal alkaline phosphatase activity. Mycorrhizai plants were grown in three-compartment systems where nylon mesh was used to separate a root-free hypha! compartment (HC) and a root-Fhyphal compartment (RHC) from the main root compartment (RC). Non-mycorrhizal control plants were gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 26 publications
1
29
0
1
Order By: Relevance
“…There are several possible reasons to explain why trees did develop P deficiency : (1) trees were planted from the commercial nursery with stored P ( 0n20 % leaf P) that was re-allocated for growth ; (2) root systems had pre-established mycorrhizal colonization when transplanted, and even though further development and activity was inhibited by benomyl, some mycorrhizal-mediated uptake of P occurred even at low P supply ; (3) slow-growing perennial Citrus on the four rootstocks had a relatively low P demand compared with supply of P that the expanding root system and mycorrhiza hyphal network had access to from the soil volume ; (4) trees were sufficient in nutrient content and otherwise well-watered and fertilized with other macronutrients and micronutrients ; or (5) soil-water status and nutrient availability in the low P-fixing Candler fine sand was not as restrictive to diffusion and mass flow of P as might be expected in finer textured soils of higher buffering capacity. The second possibility is supported by studies that indicate benomyl inhibited P uptake, transport and possibly transfer through the plantmycorrhizal fungus interface (Sukarno et al, 1993(Sukarno et al, , 1996, but benomyl did not reduce fungal alkaline phosphatase activity of G. caledonium colonizing cucumber (Larsen et al, 1996). This raises the possibility that different mycorrhizal species in the soil population vary in their sensitivity to benomyl.…”
Section: supporting
confidence: 59%
See 1 more Smart Citation
“…There are several possible reasons to explain why trees did develop P deficiency : (1) trees were planted from the commercial nursery with stored P ( 0n20 % leaf P) that was re-allocated for growth ; (2) root systems had pre-established mycorrhizal colonization when transplanted, and even though further development and activity was inhibited by benomyl, some mycorrhizal-mediated uptake of P occurred even at low P supply ; (3) slow-growing perennial Citrus on the four rootstocks had a relatively low P demand compared with supply of P that the expanding root system and mycorrhiza hyphal network had access to from the soil volume ; (4) trees were sufficient in nutrient content and otherwise well-watered and fertilized with other macronutrients and micronutrients ; or (5) soil-water status and nutrient availability in the low P-fixing Candler fine sand was not as restrictive to diffusion and mass flow of P as might be expected in finer textured soils of higher buffering capacity. The second possibility is supported by studies that indicate benomyl inhibited P uptake, transport and possibly transfer through the plantmycorrhizal fungus interface (Sukarno et al, 1993(Sukarno et al, , 1996, but benomyl did not reduce fungal alkaline phosphatase activity of G. caledonium colonizing cucumber (Larsen et al, 1996). This raises the possibility that different mycorrhizal species in the soil population vary in their sensitivity to benomyl.…”
Section: supporting
confidence: 59%
“…This reduction in P acquisition had no negative effect on growth of trees because tissue P status never dropped below the critical level of leaf P for citrus (0n10 %) during this 27-month study. Adequate P status of citrus trees was maintained with or without P fertilization and despite benomyl inhibition of extraradical and intraradical activity of mycorrhizas (Hale & Sanders, 1982 ;Larsen et al, 1996 ;Sukarno, Smith & Scott, 1993. There are several possible reasons to explain why trees did develop P deficiency : (1) trees were planted from the commercial nursery with stored P ( 0n20 % leaf P) that was re-allocated for growth ; (2) root systems had pre-established mycorrhizal colonization when transplanted, and even though further development and activity was inhibited by benomyl, some mycorrhizal-mediated uptake of P occurred even at low P supply ; (3) slow-growing perennial Citrus on the four rootstocks had a relatively low P demand compared with supply of P that the expanding root system and mycorrhiza hyphal network had access to from the soil volume ; (4) trees were sufficient in nutrient content and otherwise well-watered and fertilized with other macronutrients and micronutrients ; or (5) soil-water status and nutrient availability in the low P-fixing Candler fine sand was not as restrictive to diffusion and mass flow of P as might be expected in finer textured soils of higher buffering capacity.…”
Section: mentioning
confidence: 99%
“…Although benomyl often decreases arbuscular mycorrhizal function more than its colonization of roots (Larsen et al, 1996), no evidence was found for an impact on ericoid mycorrhizal function. The isotopic composition of leaf N (δ"&N) of V. uliginosum was unchanged by benomyl addition (Fig.…”
Section: Effects Of Benomyl On Availability Of Soil Nutrients Soil Mmentioning
confidence: 76%
“…The use of root colonization levels as a surrogate measure of mycorrhizal activity may also result in overestimation of the capacity of the AM association to enhance P uptake. Larsen et al (1996) showed that hyphal P-uptake was inhibited when benomyl was applied to an established hyphal network in soil.…”
Section: Discussionmentioning
confidence: 99%